Later medieval cross-cultural interactions : the settlement evidence in the baronies of Overk, county Kilkenny and Clanmahon, county Cavan - Shine, Linda (Trinity College (Dublin, Ireland). Department of History, 2011)
This thesis seeks to cast further light on the nature of cross-cultural interactions between the Gaelic-lrish and the Anglo-Normans in high and late medieval Ireland, by examining the archaeological evidence for settlement in two contrasting study areas. The barony of Overk, county Kilkenny was largely dominated by the Anglo-Normans during the high and late medieval period and there was a significant influx of settlers to the area. The Anglo-Normans who settled in Overk interacted with the large number of Gaelic-lrish people who remained within the barony and those who were pushed onto the fringes of the barony. This study argues that the best methodology for identifying the settlements inhabited by the Gaelic-lrish who remained within the colony is through the combination of archaeological and historical information. The barony of Clanmahon, county Cavan was largely dominated by the Gaelic-lrish but it shared a border with medieval county Meath, and the Anglo-Normans who dominated this region made a number of attempts to expand northwards into Clanmahon. Consequently, there were significant interactions, both amicable and hostile, between the Gaelic-lrish of Clanmahon and their Anglo-Norman neighbours and this thesis argues that these interactions are reflected in the settlement forms occupied by both groups in the region.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin